The Practice of Feedback in Health Professions Education in the Hierarchical and Collectivistic Culture: a Scoping Review - Soemantri, Diantha; Nurokhmanti, Hikmawati; Qomariyah, Nurul; Claramita, Mora (Springer, 2022)
The global trend in student assessment is moving towards outcome-based assessment that requires multiple systematic data points and continuous feedback. However, in hierarchical and collectivistic cultures, one-way communication is practised more often, leading to less dialogical feedback. This scoping review explored feedback practice in Asian educational setting. Based on the 17 articles selected, the findings were categorised into four themes, i.e. inhibiting or facilitating factors of feedback, influences of cultural factors on feedback, discrepancies between students’ and teachers’ perceptions of feedback and impact of feedback. Hierarchical and collectivist cultural aspects, such as preference for group feedback, are pertinent to feedback practice, which likely influence the readiness for programmatic assessment. © 2022, The Author(s) under exclusive licence to International Association of Medical Science Educators.